Quality of infant care in primary health services in Southern and Northeastern Brazil - Andréia Soprani dos Santos; Suele Manjourany Silva Duro; Nágela Valadão Cade; Luiz Augusto Facchini; Elaine Tomasi (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To assess the quality of the health care provided to children aged under one year old performed by primary health services in the South and Northeast regions of Brazil. METHODS This is a cross-sectional, population-based study carried out in 2010 with 7,915 children aged from one to four years, whose homes are located in the areas of health service coverage. We described the prevalence of procedures and guidelines, such as weight and height measurement, vaccination, newborn blood spot screening, evaluation of umbilical cord, instruction on breastfeeding and introduction of new food, and their respective 95% confidence intervals. The differences were analyzed using the chi-square test of heterogeneity and linear trend. We considered the main outcome of high-quality infant care if the child had received all recommended procedures and guidelines in the first year of life. For this analysis, we used the Poisson regression considering hierarchical model. RESULTS There was low prevalence for the instruction on breastfeeding in the first week of life (58.8%, 95%CI 57.5-60.0) and on the introduction of new food in the fourth month care. The prevalence of high-quality in childcare was 42.0% (95%CI 40.5-43.5). The adjusted analysis according to hierarchical model indicated greater probability of this outcome in the Northeast region (PR = 1.17, 95%CI 1.09-1.26), in smaller municipalities (PR = 1.17, 95%CI 1.03-1.33), and in municipalities with 50,000 and 99,000 inhabitants (PR = 1.20, 95%CI 1.09-1.34). CONCLUSIONS The Northeast region has higher-quality infant care services, which can be explained by the consolidation of the Family Health Strategy in that region.